Maternal mortality at a government teaching hospital: a six year duration study - Malipatil, Pushpanjali; V. M., Chaitanya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The studies were to help generate information and knowledge regarding the causes of maternal deaths in an urban tertiary health care government hospital and how they can be prevented in a developing country like ours to achieve millennium development goal 5 (MDGS) at reducing the MMR by 75% over the period of 1990-2015. Methods: A retrospective study done in the year of 2014 on 97 maternal deaths over a period of six years from January 2007 to December 2012. Results: During the study period there were 16,534 deliveries, and 97 maternal deaths, giving a maternal mortality rate of 586/100,000 live births. Haemorrhage was leading cause of death. Most women died within 24 hours of admission and most of them were admitted in shock. The majority of the death occurred in the age group 20-30 years and in multigravidas. Conclusions: The maternal mortality rate is much more than the national MMR. Haemorrhage was the leading cause of death followed by septicemia, both of them being preventable by adequate transfusion of blood and its components, delivery in a well-equipped hospital, early identification and prompt action, good antibiotic coverage, and early transportation.